The Development of Islamic Civilization in Iran: Persian Civilization and the Impact of Western Embargoes - Damayanti, Rizki (Journal of Al-Tamaddun, 2025)
This research aimed to investigate the dynamics of the development of Islamic civilization in Iran by exploring the complex relationship between Islam, history of Persian civilization, and impact of the Western embargo. Iran is the successor of the rich Persian civilization and has experienced significant social, political, and economic transformations since the Islamic revolution in 1979. Historical methods and contextual analysis are used to detail the development of Islam in Iran, especially in the context of Persian history. This covers the glorious period of Persian literature, art, and policy. Iran possesses an extraordinary influence in shaping world history and civilization. In addition, this research discusses the impact of the embargo imposed by Western countries in changing the economic and political dynamics of Iran. The results show that the integration of Islamic economic principles, such as social justice, equitable wealth distribution, and sustainability, has been important in the response of the country to the embargo. The interplay of Persian cultural heritage and Islamic values is reported in shaping national identity and strategic methods. A multidisciplinary theoretical framework is used to combine historical analysis, cultural analysis, and political economy theories. The method allows a comprehensive examination of religion, history, and geopolitics intersection in shaping the unique trajectory of Iran as a great Islamic civilization. By combining historical, cultural, and political analysis, this research is expected to provide a better understanding of Islam in the development of civilization, as well as the impact of Western embargo on internal and external dynamics. The results contribute to academic thinking about the interaction between religion, history, and geopolitics in the context of Iran.